Study of Treatment Methods for Surrounding Soft Tissues of Implants Following Mandibular Reconstructions with Fibula-Free Flaps - Kazuhiko Nakaue; Satoshi Horita; Mitsuhiko Imada; Kazuhiko Yamamoto; Tsutomu Sugiura; Nobuhiro Ueda; Nobuhiro Yamakawa; Yohei Nakayama; Tadaaki Kirita (MDPI AG, 2020)
In maxillofacial reconstruction implant treatment, unsatisfactory soft tissue treatment of the area around the implant may lead to inflammation. As a result, appropriate soft tissue treatment is critical. To the best of our knowledge, there are no studies that compare the different tissue treatment methods available. Hence, in this study, we compare three soft tissue treatment methods around implants after mandibular reconstruction is achieved with a fibula-free flap. Out of 33 patients who underwent mandible reconstruction using fibula-free flaps between 2006 and 2015, 5 were selected for this study. A total of 17 implants were used for treatment by the final prosthetics of the five patients. Three soft tissue treatment methods with free gingival graft (FGG) were evaluated, namely, installing a splint in a modified abutment to protect the wounded area during a palatal mucosa transplant (method 1), installing a splint or dentures to a locator abutment (method 2), and the use of screw-in fixed dentures (method 3). The method that could guarantee the widest keratinized mucosa was the screw-in fixed denture method. The results of our study indicated that employing screw-in fixed dentures for FGG may be a useful soft tissue treatment for mandible reconstruction implants.